Associations between Awareness of Sexually Transmitted Infections (STIs) and Prevalence of STIs among Sub-Saharan African Men and Women - Meghana Vasudeva; Raja Nakka; Shannon Stock; Musie Ghebremichael (Tropical Medicine and Infectious Disease, 2022)
Treatments for HIV and other STIs are not readily available in sub-Saharan Africa and other resource-limited areas, where the prevalence of HIV and other STIs is high. In the absence of treatment and laboratory infrastructure to monitor treatment efficacy, increasing awareness of STIs and STI screening are crucial components of STI prevention programs. In the current study, we sought to estimate the awareness of STIs in resource-limited countries and evaluate the strength of the association between the awareness of STIs and STIs infection. We did a secondary analysis of data obtained from 2019 women and 794 men enrolled in a community-based study that was conducted from November 2002 to March 2003 in the Moshi Urban District of Northern Tanzania. We found gonorrhea, syphilis, and HIV/AIDS were well-known among the study participants. However, their awareness of other STIs, including herpes, was very low. We also found that the awareness of STIs was not associated with STIs in men, but women who had prior knowledge of gonorrhea, syphilis, and HIV had a twofold higher risk of testing positive for an STI. Education programs aimed at increasing awareness of STIs are needed in the region. The majority of the existing STI education programs in the region focus exclusively on HIV/AIDS. The expansion of the existing AIDS/HIV education programs needs to be strengthened to include information about other STIs.